2020
DOI: 10.1002/bkcs.11975
|View full text |Cite
|
Sign up to set email alerts
|

An Invariable Temperature during the Phase Transition of W Doped VO2 Film

Abstract: The phase transition temperature of the functional VO2 films was adjusted to near room temperature by the W6+ doping. The V1−xW xO2 (0 ≤ x ≤ 0.04) films were deposited by the one‐step thermal decomposition process (30 min at 793 K) on a sapphire (0001) substrate under inert conditions. The electrical resistivity of the films showed that the ending point of the metal to insulator transition (TCE) of the pure VO2 phase transition, which appeared at ~310 K, was shifted down to ~265 K along with the increased dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The lattice distortion will enhance the insulator character of the low‐temperature phase VO 2 and will increase the T HS . This effect of Cr 3+ doped into VO 2 is completely contrary to that of W +6 doped into VO 2 : W 6+ produces V 3+ to keep the charge neutrality and destabilizes the low‐temperature VO 2 lattice, resulting in the decrease of T HS 18 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The lattice distortion will enhance the insulator character of the low‐temperature phase VO 2 and will increase the T HS . This effect of Cr 3+ doped into VO 2 is completely contrary to that of W +6 doped into VO 2 : W 6+ produces V 3+ to keep the charge neutrality and destabilizes the low‐temperature VO 2 lattice, resulting in the decrease of T HS 18 …”
Section: Resultsmentioning
confidence: 98%
“…35 K to ca. 75 K by 4 at.% of W doping 15,18 . This wider transition gap will result in a vague switching response for any device applications.…”
Section: Introductionmentioning
confidence: 99%
“…6 ). There is expected hysteresis 37 , 93 , 102 in the heating and cooling ’s. was determined from the peak maxima positions of the DSC data, and the inflection point of the magnetization data.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to a local decrease in c/a of − 0.003(2) at% −1 (Table S20) compared to an increase of 0.00027(1) at% −1 (Table S21) in the long range with the average structure lying between the two at − 0.00071 (6) at%. Most of the recent W-substitution literature 23,61,[82][83][84][85][86][87][88][89][90][91][92][93] uses average structure information to draw conclusions from, but it has been demonstrated that locally the structure changes much more drastically than the average structure indicates.…”
mentioning
confidence: 99%
“…Perovskite‐type metal oxynitrides with the general formula AB(O,N) 3 (A = Ca, Sr, Ba, or La; B Ti, Nb, and Ta) have attracted considerable attention as semiconductor materials for energy conversion and environmental treatments 1–5 . The substitution of O 2− by N 3− during the thermal ammonolysis of starting oxides significantly narrows the band‐gap energies ( E g ) of prepared oxynitrides because of their more negative valence band maximum (VBM) potentials originating from the hybridization between O 2p and Nb 2p orbitals.…”
Section: Introductionmentioning
confidence: 99%